Silicalite‐1 Encapsulated Fe Particles over an In‐situ Crystal Process for Syngas to Gasoline with Low CO2 Selectivity. Issue 48 (21st December 2018) - Cheng, Shilin; Mazonde, Brighton; Zhang, Guihua; Javed, Mudassar; Amoo, Cederick; Shi, Yanwen; Guo, Kailiang; Yao, Miaohong; Lu, Chengxue; Yang, Guohui; Yang, Ruiqin; Xing, Chuang
Abstract: Zeolite synthesis involved use of large volumes of solvent that resulted in waste and enhanced production costs. In our study, we selected a solvent‐free synthesis route that involved mixing, grinding and crystallization at various times creating Fe@Silicalite‐1. This synthesis method produced a hierarchical in‐situ microporous crystal morphology with Fe particles caged inside zeolite displaying a high gasoline (C5 ‐C11 ) selectivity of 66.0% with a relatively low CO2 and CH4 selectivity (18.5% and 10.0%, respectively) in Fischer‐Tropsch synthesis. Prolonged crystallization time of 72 h and other subsequent procedures contributed to zeolite structure and performance. Iron moieties were appropriately immobilized over silicalite support. The characterization results were correlated with the zeolite activity and selectivity. This novel zeolite at its best possesses all the potential to be advanced in other related material synthesis because of its expedient procedure, characteristics and worthwhile outcomes. Abstract : As a result of solvent‐free synthesis route, this Fe@Silicalite‐1 zeolite containing hierarchical in‐situ microporous crystal structure in union with Fe particles entrapped within zeolite contributed largely to gasoline product distribution of Fischer‐Tropsch synthesis reaction. The remarkable high gasoline selectivity of 66.0% has been achieved by this zeolite as a result of its intrinsic properties.